Emprego de microextração líquido-líquido dispersiva em mel para posterior determinação de cádmio e chumbo por espectrometria de absorção atômica com chama - Rosa, Francisco Cunha da (2014)
Honey has become an important environmental indicator, due to its various botanical and geographical sources, since bees come into contact with different environments that could be contaminated with toxic elements. Among these contaminants, Cd and Pb represent potential health risks of life. Additionally, in order to control the human exposition to contaminated honey, the Brazilian Ministry of Agriculture, Livestock and Supply determines 500 ng g-1 as the maximum allowable limits for Cd and Pb in honey. Once relatively low concentrations of Cd and Pb are present in honey samples, it is necessary to use powerful detection methods in order to allow its quantification of However, even considering a sensitive technique as ICP-MS, the main problem is still the sample preparation methods, which normally employ relatively high temperature and dangerous acids. Additionally, this step is considered time and reagent consuming, generating high amount of residues. In this sense, the present work proposes the use of dispersive liquid-liquid microextraction (DLLME) on aqueous samples of honey for extraction and pre-concentration of Cd and Pb, with subsequent determination by F AAS. As the main advantage provided by developed method (DLLME - F AAS), it is simple, fast and reliable. After optimization of experimental conditions, limit of detection of 18 ng g-1 for Cd and 135 ng g-1 for Pb were obtained. These results are similar to those obtained using ICP-MS with wet digestion sample preparation using oxidant acids. Furthermore, it is important to mention that these limits are lower than those established by the Ministry of Agriculture (500 ng g-1 for Cd and Pb), which represents a promising method for routine analysis in food, to meet the regulations. It avoid the use of huge amount of concentrates acids, minimizing the generation of residues, fast and low cost.